The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1090/mcom/3158
|View full text |Cite
|
Sign up to set email alerts
|

Finite element exterior calculus with lower-order terms

Abstract: Abstract. The scalar and vector Laplacians are basic operators in physics and engineering. In applications, they frequently show up perturbed by lowerorder terms. The effect of such perturbations on mixed finite element methods in the scalar case is well-understood, but that in the vector case is not. In this paper, we first show that, surprisingly, for certain elements there is degradation of the convergence rates with certain lower-order terms even when both the solution and the data are smooth. We then give… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Last, by means of the Bernoulli functions, the resulting schemes are shown to converge to special upwind schemes as the diffusion coefficient approaches to zero. The SAFE schemes also provide a promising way to discrete the Lie convection with Hodge Laplacian [2].The rest of the paper is organized as follows. In Section 2 we introduce the general convection-diffusion problems and briefly review the P − 1 Λ k discrete de Rham complex.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Last, by means of the Bernoulli functions, the resulting schemes are shown to converge to special upwind schemes as the diffusion coefficient approaches to zero. The SAFE schemes also provide a promising way to discrete the Lie convection with Hodge Laplacian [2].The rest of the paper is organized as follows. In Section 2 we introduce the general convection-diffusion problems and briefly review the P − 1 Λ k discrete de Rham complex.…”
mentioning
confidence: 99%
“…Last, by means of the Bernoulli functions, the resulting schemes are shown to converge to special upwind schemes as the diffusion coefficient approaches to zero. The SAFE schemes also provide a promising way to discrete the Lie convection with Hodge Laplacian [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Use of the IGAFEM to analyse a 3D solid presents challenges since it requires a volumetric NURBS description, which is not trivial to generate. There have been some early works injecting spline functions into the BEM, many of which predated the IGAFEM [12][13][14][15][16][17][18]. Simpson et al [19,20] applied the isogeometric concept in a BEM framework, and found similar benefits over classical piecewise polynomial formulations.…”
Section: Introductionmentioning
confidence: 99%
“…In view of literature on traditional mixed methods and MFEMs in FEEC, researchers are more concerned with errors measured in the L 2 -norm · or the V -norm · HΛ . For example, the authors in [3,4] made a great effort to obtain improved decoupled a priori error estimates for σ − σ h and u − u h . The contributions of this paper are listed as follows.…”
mentioning
confidence: 99%